Efficacy and Safety of Therapeutic Plasma Exchange in Children with Neuroimmunological Disorders: A Limited Unicentral Study - Nikkhah, Ali; Nasehi, Mohammad Mahdi; Momtazmanesh, Nader; Etemad, Kourosh; Hajatnia, Somayeh (Iranian Journal of Child Neurology, 2024)
Objectives Therapeutic plasma exchange (TPE) is a plasmapheresis procedure whose Safety data for pediatric neuro-immunological disorders (PNID) is confined. The present research documents TPE’s safety and feasibility data in these conditions. Materials & Methods The current study involved six distinct groups of patients with PNID undergoing TPE: neuromyelitis optic spectrum disorder (NMOSD), autoimmune encephalitis (AIE), acute disseminated encephalomyelitis (ADEM), multiple sclerosis (MS), Guillain-Barre syndrome (GBS), and optic neuritis (ON). This study documented complications related to each TPE process. In addition, TPE’s efficacy was studied in these patients. Results The present study recorded adverse effects in 18 patients with PNID that received 121 TPE cycles: five cycles (4.13%) in MS, three(2.48%) in AIE subgroup, one (0.82%) in ADEM, and two (1.65%) in GBS. No severe complications were observed among the patients. Conclusion Patients with PNID tolerated therapeutic plasma exchange, which was a safe process.